Ecological niche modelling of cold-water corals in the Southern Ocean (N Antarctic), present distribution and future projections due to temperature changes - Chaabani, Safa; López-González, Pablo J; Casado-Amezua, Pilar; Pehlke, Hendrik; Weber, Lukas; Martínez-Baraldés, Irene; Jerosch, Kerstin (Marine Ecology Progress Series, 2019)
An urgent necessity to understand the effect of climatic change on scleractinian cold-water coral (CWC) ecosystems has arisen due to increasing ocean warming and acidification over the last decades. Here, presence-absence records of 12 scleractinian CWC species from research expeditions and the literature were compiled and merged with model-generated pseudo-absence data and 14 environmental variables. The best-fitting results of 9 species distribution models (SDMs) were combined to an ensemble habitat suitability model for CWCs in the northern Southern Ocean (Weddell Sea and Antarctic Peninsula) by means of the open-source R package "biomod2". Furthermore, 2 future scenarios of increasing bottom sea temperature were used to investigate the spatial response of scleractinians to temperature change. The resulting (current scenario) potential ecological niches were evaluated with good to excellent statistical measures. The results predict that present areas of highest probability of CWC occurrence are around the Antarctic Peninsula, South Orkney Islands and Queen Maud Land, with preference to geomorphic features such as seamounts. The distribution of CWC habitats is mainly driven by distance to coast and ice shelves, bathymetry, benthic calcium carbonate, and temperature. Under warming conditions, CWCs are predicted to expand their distribution range by 6 and 10% in 2037 and 2150, respectively, compared to the present distribution. The future models using increased bottom temperature revealed a stable CWC distribution for most parts of the study area. However, habitat shifts are expected to the Filchner Trough region, the adjacent continental shelves, as well as to the eastern side of the Antarctic Peninsula. KEYWORDS: Scleractinian coral · Ensemble models · Environmental change · Habitat suitability model · Spatial distribution · Weddell Sea. Antarctica
Keywords: Sørishavet; Weddellhavet; batymetri; biodiversitet; global oppvarming; klimaendringer; marin biologi; miljøendringer; oseanografi; økosystemer

Very Strong Atmospheric Methane Growth in the 4 Years 2014–2017: Implications for the Paris Agreement - Nisbet, Euan G; Manning, Martin; Dlugokencky, Ed; Fisher, Rebecca; Lowry, Dave; Michel, Sylvia; Myhre, Cathrine Lund; Platt, Stephen Matthew; Allen, Grant; Bousquet, Philippe; Brownlow, Rebecca; Cain, Michelle; et al. (Global Biogeochemical Cycles, 2019)
Atmospheric methane grew very rapidly in 2014 (12.7 ± 0.5 ppb/year), 2015 (10.1 ± 0.7 ppb/year), 2016 (7.0 ± 0.7 ppb/year), and 2017 (7.7 ± 0.7 ppb/year), at rates not observed since the 1980s. The increase in the methane burden began in 2007, with the mean global mole fraction in remote surface background air rising from about 1,775 ppb in 2006 to 1,850 ppb in 2017. Simultaneously the 13C/12C isotopic ratio (expressed as δ13CCH4) has shifted, now trending negative for more than a decade. The causes of methane's recent mole fraction increase are therefore either a change in the relative proportions (and totals) of emissions from biogenic and thermogenic and pyrogenic sources, especially in the tropics and subtropics, or a decline in the atmospheric sink of methane, or both. Unfortunately, with limited measurement data sets, it is not currently possible to be more definitive. The climate warming impact of the observed methane increase over the past decade, if continued at >5 ppb/year in the coming decades, is sufficient to challenge the Paris Agreement, which requires sharp cuts in the atmospheric methane burden. However, anthropogenic methane emissions are relatively very large and thus offer attractive targets for rapid reduction, which are essential if the Paris Agreement aims are to be attained.
Keywords: Antarktis; atmosfæren; atmosfærisk metan; fossilt brensel; global klimamodell; global oppvarming; klimaendringer; klimagasser; metanisotoper; metanutslipp; meteorologi; polarområdene

On the long-ignored scientific achievements of the Belgica expedition 1897–1899 - De Deckker, Patrick (Polar Research, 2018)
The Belgica expedition, which left Belgium in August 1897, was the first to spend 13 months continuously in Antarctic waters, before returning in late 1899. This was not only an exploratory venture, as new lands and oceans were charted, but more importantly it was an exceptional and successful scientific voyage. After the return of the expedition, a vast array of scientific data was processed and eventually 92 publications in some nine volumes funded by the Belgica Commission appeared over 40 years as a series called Résultats du voyage de la Belgica en 1897–99 sous le commandement de A. de Gerlache de Gomery – rapports scientifiques. Disappointingly, those significant results have been mostly ignored in the scientific literature and the paper here aims to inform scientists of the achievements of the Belgica expedition and where to obtain the information. Many of the climatological and oceanographic data obtained by the expeditioners ought to be examined in line with the changes that are occurring today in the Antarctic Peninsula region as a result of global warming. Some of the Belgica data form an important database to critically assess environmental changes over 120 years in the region of the Antarctic Peninsula.
Keywords: Antarktis; Belgica ekspedisjon; glasiologi; global oppvarming; klimaendringer; klimatologi; meteorologi; miljøendringer; oppdagelsesreiser; oseanografi; vitenskap

Observation-Based Trends of the Southern Ocean Carbon Sink - Ritter, Rebecca; Landschützer, Peter; Gruber, Nicolas; Fay, Amanda R; Iida, Yosuke; Jones, Stephen Daniel; Nakaoka, Shin-ichiro; Park, Geun-Ha; Peylin, Philippe; Rödenbeck, Christian; Rodgers, Keith B; Shutler, Jamie D; et al. (Geophysical Research Letters, 2017)
The Southern Ocean (SO) carbon sink has strengthened substantially since the year 2000, following a decade of a weakening trend. However, the surface ocean pCO2 data underlying this trend reversal are sparse, requiring a substantial amount of extrapolation to map the data. Here we use nine different pCO2 mapping products to investigate the SO trends and their sensitivity to the mapping procedure. We find a robust temporal coherence for the entire SO, with eight of the nine products agreeing on the sign of the decadal trends, that is, a weakening CO2 sink trend in the 1990s (on average 0.22 ± 0.24 Pg C yr−1 decade−1), and a strengthening sink trend during the 2000s (−0.35 ± 0.23 Pg C yr−1 decade−1). Spatially, the multiproduct mean reveals rather uniform trends, but the confidence is limited, given the small number of statistically significant trends from the individual products, particularly during the data-sparse 1990–1999 period.
Keywords: Sørishavet; biogeokjemi; global oppvarming; karbondioksid; klimaendringer; klimatologi; meteorologi

A constitutive framework for predicting weakening and reduced buttressing of ice shelves based on observations of the progressive deterioration of the remnant Larsen B Ice Shelf - Borstad, Chris; Khazendar, Ala; Scheuchl, Bernd; Morlighem, Mathieu; Larour, Eric; Rignot, Eric (Geophysical Research Letters, 2016)
The increasing contribution of the Antarctic Ice Sheet to sea level rise is linked to reductions in ice shelf buttressing, driven in large part by basal melting of ice shelves. These ocean-driven buttressing losses are being compounded as ice shelves weaken and fracture. To date, model projections of ice sheet evolution have not accounted for weakening ice shelves. Here we present the first constitutive framework for ice deformation that explicitly includes mechanical weakening, based on observations of the progressive degradation of the remnant Larsen B Ice Shelf from 2000 to 2015. We implement this framework in an ice sheet model and are able to reproduce most of the observed weakening of the ice shelf. In addition to predicting ice shelf weakening and reduced buttressing, this new framework opens the door for improved understanding and predictions of iceberg calving, meltwater routing and hydrofracture, and ice shelf collapse.
Keywords: Antarktis; glasiologi; global oppvarming; havnivåstigning; innlandsis; isbrem; isshelf; smelting

Den langsomme polare vippen - Sorokina, Svetlana (Naturen, 2016)
De siste 20 årene har vært de varmeste siden globale temperaturmålinger startet i 1880 (Figur 1). FNs klimapanel konkluderer med at hovedårsaken til den observerte temperaturøkningen er menneskeskapte utslipp av klimagasser. I nordområdene har temperaturen økt nesten dobbelt så raskt som i resten av verden. Isdekket er nær halvert og isvolumet er redusert til en tredjedel. Men på den andre siden av jorden, altså i Antarktis, er situasjonen en helt annen. Temperaturen har vært fallende de siste årene og isdekket har vært rekordstort. Dette paradokset brukes ofte som et argument mot menneskeskapte endring av klima. For hvordan kan det ha seg at temperaturen i Antarktis faller når klimagassutslippene øker?
Keywords: Antarktis; global oppvarming; klimaendringer; klimagasser; polarområdene

Methane and nitrous oxide fluxes in relation to vegetation covers and bird activity in ice-free soils of Rip Point, Nelson Island, Antarctica - Neufeld, Ângela Denise Hubert; de Godoi, Stefânia Guedes; Pereira, Antônio Batista; Bayer, Cimélio; Schünemann, Andriano Luis; de Carvalho Victoria, Filipe; de Albuquerque, Margéli Pereira; Camargo, Estefânia; Vieira, Frederico Costa Beber (Polar Research, 2015)
This study aimed to quantify the nitrous oxide (N2O) and methane (CH4) fluxes at sites with different vegetation covers and where bird activity was present or absent using the static chamber method, on Rip Point, Nelson Island, maritime Antarctic. The sites were soils covered by Sanionia uncinata, lichens, Prasiola crispa, Deschampsia antarctica and bare soil. Seabirds used the P. crispa and D. antarctica sites as nesting areas. Soil mineral N contents, air and soil temperature and water-filled pore space were measured, and the content of total organic C and particulate organic C, total N, bulk density and texture were determined to identify controlling variables of the gas emissions. The N2O and CH4 flux rates were low for all sampling events. Mean N2O flux rates ranged from 0.11±1.93 up to 21.25±22.14 µg N2O m−2 h−1 for the soils under lichen and P. crispa cover, respectively. For the CH4 fluxes, only the P. crispa site showed a low positive mean (0.47±3.61 µg CH4 m−2 h−1). The bare soil showed the greatest absorption of CH4 (−11.92±5.7 µg CH4 m−2 h−1), probably favoured by the coarse soil texture. Bare soil and S. uncinata sites had N2O accumulated emissions close to zero. Net CH4 accumulated emission was observed only at the P. crispa site, which was correlated with (p<0.001). These results indicate that seabird activity influences N2O and CH4 soil fluxes, while vegetation has little influence, and bare soil areas in maritime Antarctica could be greenhouse gas sinks. Keywords: Soil greenhouse gases; seabirds; vegetal cover; maritime Antarctica.
Keywords: Antarktis; biogeokjemi; drivhuseffekt; drivhusgasser; flora; global oppvarming; klimaendringer; klimagasser; planter; sjøfugler; økosystemer

Counteracting the climate effects of volcanic eruptions using short-lived greenhouse gases - Fuglestvedt, Jan S.; Samset, Bjørn H.; Shine, Keith P. (Geophysical Research Letters, 2014)
A large volcanic eruption might constitute a climate emergency, significantly altering global temperature and precipitation for several years. Major future eruptions will occur, but their size or timing cannot be predicted. We show, for the first time, that it may be possible to counteract these climate effects through deliberate emissions of short-lived greenhouse gases, dampening the abrupt impact of an eruption. We estimate an emission pathway countering a hypothetical eruption 3 times the size of Mount Pinatubo in 1991. We use a global climate model to evaluate global and regional responses to the eruption, with and without counteremissions. We then raise practical, financial, and ethical questions related to such a strategy. Unlike the more commonly discussed geoengineering to mitigate warming from long-lived greenhouse gases, designed emissions to counter temporary cooling would not have the disadvantage of needing to be sustained over long periods. Nevertheless, implementation would still face significant challenges.
Keywords: Antarktis; drivhusgasser; global klimamodell; global oppvarming; klimatologi; nedbør; polarområdene; vulkaner

The impact of abrupt suspension of solar radiation management (termination effect) in experiment G2 of the Geoengineering Model Intercomparison Project (GeoMIP) - Jones, Andy; Haywood, Jim M; Alterskjær, Kari; Boucher, Olivier; Cole, Jason N S; Curry, Charles L; Irvine, Peter J; Ji, Duoying; Kravitz, Ben; Egill Kristjánsson, Jón; Moore, John C; Niemeier, Ulrike; et al. (Journal of Geophysical Research: Atmospheres, 2013)
We have examined changes in climate which result from the sudden termination of geoengineering after 50 years of offsetting a 1% per annum increase in CO2 concentrations by a reduction of solar radiation, as simulated by 11 different climate models in experiment G2 of the Geoengineering Model Intercomparison Project. The models agree on a rapid increase in global-mean temperature following termination accompanied by increases in global-mean precipitation rate and decreases in sea-ice cover. There is no agreement on the impact of geoengineering termination on the rate of change of global-mean plant net primary productivity. There is a considerable degree of consensus for the geographical distribution of temperature change following termination, with faster warming at high latitudes and over land. There is also considerable agreement regarding the distribution of reductions in Arctic sea-ice, but less so for the Antarctic. There is much less agreement regarding the patterns of change in precipitation and net primary productivity, with a greater degree of consensus at higher latitudes.
Keywords: Antarktis; global oppvarming; karbondioksid; klimaendringer; klimamodeller; klimatologi; polarområdene; solstråling

Recent snowfall anomalies in Dronning Maud Land, East Antarctica, in a historical and future climate perspective - Lenaerts, Jan T M; van Meijgaard, Erik; van den Broeke, Michiel R; Ligtenberg, Stefan R M; Horwath, Martin; Isaksson, Elisabeth (Geophysical Research Letters, 2013)
Enhanced snowfall on the East Antarctic ice sheet is projected to significantly mitigate 21st century global sea level rise. In recent years (2009 and 2011), regionally extreme snowfall anomalies in Dronning Maud Land, in the Atlantic sector of East Antarctica, have been observed. It has been unclear, however, whether these anomalies can be ascribed to natural decadal variability, or whether they could signal the beginning of a long-term increase of snowfall. Here we use output of a regional atmospheric climate model, evaluated with available firn core records and gravimetry observations, and show that such episodes had not been seen previously in the satellite climate data era (1979). Comparisons with historical data that originate from firn cores, one with records extending back to the 18th century, confirm that accumulation anomalies of this scale have not occurred in the past ~60 years, although comparable anomalies are found further back in time. We examined several regional climate model projections, describing various warming scenarios into the 21st century. Anomalies with magnitudes similar to the recently observed ones were not present in the model output for the current climate, but were found increasingly probable toward the end of the 21st century.
Keywords: Dronning Maud Land; glasiologi; global oppvarming; havnivåstigning; innlandsis; klimaendringer; klimatologi

Can we use ice sheet reconstructions to constrain meltwater for deglacial simulations? - Bethke, Ingo; Li, Camille; Nisancioglu, Kerim H (Paleoceanography, 2012)
Freshwater pulses from melting ice sheets are thought to be important for driving deglacial climate variability. This study investigates challenges in simulating and understanding deglacial climate evolution within this framework, with emphasis on uncertainties in the ocean overturning sensitivity to meltwater inputs. The response of an intermediate complexity model to a single Northern Hemisphere meltwater pulse is familiar: a weakening of the ocean overturning circulation in conjunction with an expansion of sea ice cover and a meridional temperature seesaw. Nonlinear processes are vital in shaping this response and are found to have a decisive influence when more complex scenarios with a history of pulses are involved. A meltwater history for the last deglaciation (21–9 ka) was computed from the ICE-5G ice sheet reconstruction, and the meltwater was routed into the ocean through idealized ice sheet drainages. Forced with this meltwater history, model configurations with altered freshwater sensitivity produce a range of outcomes for the deglaciation, from those in which there is a complete collapse of the overturning circulation to those in which the overturning circulation weakens slightly. The different outcomes are interpreted in terms of the changing hysteresis behavior of the overturning circulation (i.e., non-stationary freshwater sensitivity) as the background climate warms through the course of the deglaciation. The study illustrates that current uncertainties in model sensitivity are limiting in efforts to forward-model deglacial climate variability. Furthermore, ice sheet reconstructions are shown to provide poor constraints on meltwater forcing for simulating the deglaciation.
Keywords: Sørishavet; global oppvarming; havnivåstigning; innlandsis; isavsmelting; klimamodeller; klimatologi; polarområdene; smeltevann

Review of Tourism and change in polar regions: climate, environment and experience and Cruise tourism in polar regions: promoting environmental and social sustainability? - Capelotti, P J (Polar Research, 2011)
These two edited volumes, which cover much of the same ground, both begin from a common premise: polar tourism, as its been experienced by wealthy travellers for over a century, has a very definite shelf life. With the acceleration of global climate change, the Arctic and Antarctic are being changed, changed rapidly, perhaps permanently and, if one pays attention to the news, seemingly by the day. When combined with popular documentaries and feature films like An inconvenient truth, March of the penguins and Happy feet potential polar tourists have been sensitized to see the polar regions not as implacably hostile wastes once challenged only by the likes of Nansen, Amundsen, Scott and Shackleton but as irreplaceably fragile zones that, once lost, will take some essential part of the planet with them.
Keywords: Antarktis; bokanmeldelser; cruiseturisme; global oppvarming; klimaendringer; miljøvern; polarområdene; turisme; økologi

Polythermal glacier hydrology: a review - Irvine-Fynn, Tristram D L; Hodson, Andrew J; Moorman, Brian J; Vatne, Geir; Hubbard, Alun L (Reviews of Geophysics, 2011)
The manner by which meltwater drains through a glacier is critical to ice dynamics, runoff characteristics, and water quality. However, much of the contemporary knowledge relating to glacier hydrology has been based upon, and conditioned by, understanding gleaned from temperate valley glaciers. Globally, a significant proportion of glaciers and ice sheets exhibit nontemperate thermal regimes. The recent, growing concern over the future response of polar glaciers and ice sheets to forecasts of a warming climate and lengthening summer melt season necessitates recognition of the hydrological processes in these nontemperate ice masses. It is therefore timely to present an accessible review of the scientific progress in glacial hydrology where nontemperate conditions are dominant. This review provides an appraisal of the glaciological literature from nontemperate glaciers, examining supraglacial, englacial, and subglacial environments in sequence and their role in hydrological processes within glacierized catchments. In particular, the variability and complexity in glacier thermal regimes are discussed, illustrating how a unified model of drainage architecture is likely to remain elusive due to structural controls on the presence of water. Cold ice near glacier surfaces may reduce meltwater flux into the glacier interior, but observations suggest that the transient thermal layer of near surface ice holds a hydrological role as a depth-limited aquifer. Englacial flowpaths may arise from the deep incision of supraglacial streams or the propagation of hydrofractures, forms which are readily able to handle varied meltwater discharge or act as locations for water storage, and result in spatially discrete delivery of water to the subglacial environment. The influence of such drainage routes on seasonal meltwater release is explored, with reference to summer season upwellings and winter icing formation. Moreover, clear analogies emerge between nontemperate valley glacier and ice sheet hydrology, the discussion of which indicates how persistent reassessment of our conceptualization of glacier drainage systems is required. There is a clear emphasis that continued, integrated endeavors focused on process glaciology at nontemperate glaciers are a scientific imperative to augmenting the existing body of research centered on ice mass hydrology.
Keywords: Antarktis; geografi; glasiologi; global oppvarming; hydrologi; innlandsis; isbreer; isbrem; polarområdene

Overvåking av havklima i Antarktis - Strand, Kjersti Opstad; Østerhus, Svein; Gammelsrød, Tor (Klima : norsk magasin for klimaforskning, 2011)
Publisher: CICERO senter for klimaforskning Place: Oslo
Keywords: Sørishavet; global oppvarming; havnivåstigning; klimaendringer

Atmospheric histories and global emissions of the anthropogenic hydrofluorocarbons HFC-365mfc, HFC-245fa, HFC-227ea, and HFC-236fa - Vollmer, Martin K; Miller, Benjamin R; Rigby, Matthew; Reimann, Stefan; Mühle, Jens; Krummel, Paul B; O'Doherty, Simon; Kim, Jooil; Rhee, Tae Siek; Weiss, Ray F; Fraser, Paul J; Simmonds, Peter G; et al. (Journal of Geophysical Research: Atmospheres, 2011)
We report on ground-based atmospheric measurements and emission estimates of the four anthropogenic hydrofluorocarbons (HFCs) HFC-365mfc (CH3CF2CH2CF3, 1,1,1,3,3-pentafluorobutane), HFC-245fa (CHF2CH2CF3, 1,1,1,3,3-pentafluoropropane), HFC-227ea (CF3CHFCF3, 1,1,1,2,3,3,3-heptafluoropropane), and HFC-236fa (CF3CH2CF3, 1,1,1,3,3,3-hexafluoropropane). In situ measurements are from the global monitoring sites of the Advanced Global Atmospheric Gases Experiment (AGAGE), the System for Observations of Halogenated Greenhouse Gases in Europe (SOGE), and Gosan (South Korea). We include the first halocarbon flask sample measurements from the Antarctic research stations King Sejong and Troll. We also present measurements of archived air samples from both hemispheres back to the 1970s. We use a two-dimensional atmospheric transport model to simulate global atmospheric abundances and to estimate global emissions. HFC-365mfc and HFC-245fa first appeared in the atmosphere only ∼1 decade ago; they have grown rapidly to globally averaged dry air mole fractions of 0.53 ppt (in parts per trillion, 10−12) and 1.1 ppt, respectively, by the end of 2010. In contrast, HFC-227ea first appeared in the global atmosphere in the 1980s and has since grown to ∼0.58 ppt. We report the first measurements of HFC-236fa in the atmosphere. This long-lived compound was present in the atmosphere at only 0.074 ppt in 2010. All four substances exhibit yearly growth rates of >8% yr−1 at the end of 2010. We find rapidly increasing emissions for the foam-blowing compounds HFC-365mfc and HFC-245fa starting in ∼2002. After peaking in 2006 (HFC-365mfc: 3.2 kt yr−1, HFC-245fa: 6.5 kt yr−1), emissions began to decline. Our results for these two compounds suggest that recent estimates from long-term projections (to the late 21st century) have strongly overestimated emissions for the early years of the projections (∼2005–2010). Global HFC-227ea and HFC-236fa emissions have grown to average values of 2.4 kt yr−1 and 0.18 kt yr−1 over the 2008–2010 period, respectively.
Keywords: Dronning Maud Land; atmosfæren; drivhusgasser; global oppvarming; klimaendringer; klimatologi; målinger